Distinct binding properties distinguish LQ-type calmodulin-binding domains in cyclic nucleotide-gated channels - Ungerer, Nicole; Frings, Stephan; Möhrlen, Frank (Biochemistry, 2011)
Cyclic nucleotide-gated (CNG) channels operate as transduction channels in photoreceptors and olfactory receptor neurons. Direct binding of cGMP or cAMP opens these channels which conduct a mixture of monovalent cations and Ca2+. Upon activation, CNG channels generate intracellular Ca2+ signals that play pivotal roles in the transduction cascades of the visual and olfactory systems. Channel activity is controlled by negative feedback mechanisms that involve Ca2+-calmodulin, for which all CNG channels possess binding sites. Here we compare the binding properties of the two LQ-type calmodulin binding sites, both of which are thought to be involved in channel regulation. They reside on the isoforms CNGB1 and CNGA4. The CNGB1 subunit is present in rod photoreceptors and olfactory receptor neurons. The CNGA4 subunit is only expressed in olfactory receptor neurons, and there are conflicting results as to its role in calmodulin-mediated feedback inhibition. We examined the interaction of Ca2+-calmodulin with two recombinant proteins that encompass either of the two LQ sites. Comparing binding properties, we found that the LQ site of CNGB1 binds Ca2+-calmodulin at 10-fold lower Ca2+ levels than the LQ site of CNGA4. Our data provide biochemical evidence against a contribution of CNGA4 to feedback inhibition. In accordance with previous work on photoreceptor CNG channels, our results indicate that feedback control is the exclusive role of the B-subunits in photoreceptors and olfactory receptor neurons.
Gesehen am 29.05.2017